Early warning signals of sudden changes in daily step count: an intensive longitudinal study of over 20,000 adults - Dario Baretta; Alexandre Mazéas; Aïna Chalabaev; Jennifer Inauen; Guillaume Chevance (npj Exercise Medicine and Health, 2026)
Abstract Health-protecting behaviors such as physical activity are crucial for health, yet positive behavior changes are often accompanied by setbacks and relapses. Previous research suggests that critical fluctuations in behavioral time series might foreshadow relapses as early warning signals. This study examines the association between critical fluctuations, quantified as dynamic complexity (DC), and impending sudden changes in physical activity, here walking behavior. We analyzed step count data from 21,425 participants during enrollment in a digital physical activity intervention, covering a total of 5,474,501 person-days. Step counts were recorded via smartphones or wearables. Generalized multilevel models revealed a positive association between DC and impending sudden losses in walking (odds ratios [OR] 1.93–1.32). In contrast, the association between DC and impending sudden gains was weaker and less consistent (OR = 1.10–0.89). These findings provide evidence for the role of critical fluctuations as early warning signals for sudden losses in walking behavior and highlight their potential in designing timely and targeted interventions, notably just-in-time adaptive interventions.